2022
DOI: 10.20944/preprints202212.0195.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learning based Prediction of Pain Response to Palliative Radiation Therapy - is there a Role for Planning CT-based Radiomics and Semantic Imaging Features?

Abstract: Background: Painful spinal bone metastases (PSBMs) patients regularly receive palliative radiation therapy (RT) with response rates in about 2 of 3 patients. In this exploratory study, we evaluated the value of machine learning (ML) models based on radiomic, semantic and clinical features to predict complete pain response. Methods: Gross tumour volumes (GTV) and clinical target volumes (CTV) of 261 PSBMs were segmented on planning computed tomography (CT) scans. Radiomic, semantic and clinical features were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Apart from conventional dosimetric approaches, sophisticated methods such as machine learning gain more and more importance for radiation oncology. In recent years, it has been shown that spatial quantitative features assessing the image grey-level distribution extracted from medical imaging data (radiomics) allow for unprecedented predictions of clinical endpoints including patient survival, disease progression, tumor characterization, tumor response and tumor detection ( 9 17 ). Analysis using spatial features of the dose distribution or image grey-level distributions, referred to as dosiomics ( 18 22 ) or radiomics ( 23 25 ) and even the combination of both ( 26 , 27 ) have also been successfully investigated for prediction of lung toxicity after thoracic radiotherapy in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from conventional dosimetric approaches, sophisticated methods such as machine learning gain more and more importance for radiation oncology. In recent years, it has been shown that spatial quantitative features assessing the image grey-level distribution extracted from medical imaging data (radiomics) allow for unprecedented predictions of clinical endpoints including patient survival, disease progression, tumor characterization, tumor response and tumor detection ( 9 17 ). Analysis using spatial features of the dose distribution or image grey-level distributions, referred to as dosiomics ( 18 22 ) or radiomics ( 23 25 ) and even the combination of both ( 26 , 27 ) have also been successfully investigated for prediction of lung toxicity after thoracic radiotherapy in previous studies.…”
Section: Introductionmentioning
confidence: 99%